TESTING THE MOVING AVERAGE CONVERGENCE DIVERGENCE RULES USING SUCORINVEST SHARIA EQUITY FUND - MANUNGGAL, BAGUS; PRIAMBODO P.S., YUDI (International Journal of Business, Law, and Education, 2021)
The article testing Moving Average Convergence Divergence on Sucorinvest Sharia Equity Fund. We set MACD using 60-periode for fast EMA, 130-periode for slow EMA, and 45-periode for Signal. The rule is histogram of MACD crosses zero line from below indicate buy signal and corsses zero line from above indicate sell signal. We use 8-year data from pusatdata.kontan.co.id. The result is MACD rule generate more profit than buy-and-hold strategy.